2009
DOI: 10.1021/ja809733c
|View full text |Cite
|
Sign up to set email alerts
|

Catechols as Membrane Anion Transporters

Abstract: Compounds that transport ions across cell membranes may function as sensors, signal transducers, or antimicrobials. Synthetic transporters may also help us understand how natural systems move ions across hydrophobic barriers. 1 There is an interest in identifying compounds that transport anions, especially Cl -, across lipid membranes. 2 Reports that catechol 1 binds Cl -in organic solvents prompted us to use this group to form new anion transporters. 3,4 While bacterial siderophores and synthetic analogues us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
72
0
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(77 citation statements)
references
References 23 publications
3
72
0
2
Order By: Relevance
“…All the available urea NH groups were found to be involved in hydrogen bonding the carbonate (N-O distances 2.726(2)-3.368(2)Å, N-H/O angles 139.0-166. 9 ). It appears that in the solid state the meta-nitro group does not hinder guest inclusion.…”
Section: Solid Statementioning
confidence: 99%
See 1 more Smart Citation
“…All the available urea NH groups were found to be involved in hydrogen bonding the carbonate (N-O distances 2.726(2)-3.368(2)Å, N-H/O angles 139.0-166. 9 ). It appears that in the solid state the meta-nitro group does not hinder guest inclusion.…”
Section: Solid Statementioning
confidence: 99%
“…8 amphiphilic catechols and monoacylglycerols, 9 preorganised isophthalamides and squaramides, 10 and tripodal tris(aminoethyl)amine (tren) thioureas.…”
mentioning
confidence: 99%
“…Davis and co-workers have reported that tren-based receptors with appended catechol groups are capable of transmembrane chloride transport. 8 In this communication we describe the anion transport properties of a series of simple tris-ureas and tris-thioureas based on the 30 tren scaffold 1-4.…”
mentioning
confidence: 99%
“…We used an HPTS fluorescence assay to study whether the compounds function as HCl co-transporters with nitrate as the external anion. 8 Studies were conducted at 4% molar carrier to lipid concentration. For compounds 2, 3 and 4 we found that the internal pH rises initially and then drifts down over the 15 course of the experiment (see Fig.…”
mentioning
confidence: 99%
“…TREA derivatives have been studied extensively in the field of coordination chemistry; however, little is known about their biological activities. To our knowledge, some TREA derivatives have been reported to work as membrane anion transporters 15,16) or as HIV-1 protease inhibitors. 17) In addition to these previous results, the flexibility of a TREA scaffold may enable recognition of the sites of target biological molecules, and this possibility prompted us to select TREA as a template for target tripodal-type molecules.…”
mentioning
confidence: 99%